Slew rate enhancement based on use of squaring circuits. Issue 3 (1st February 2015) - Valero, M.R.; Thoutam, S.; Ramírez‐Angulo, J.; Lopez‐Martín, A.; Carvajal, R.G.
Abstract : A squaring circuit is introduced that boosts the tail current source of an opamp to improve its slew rate. It operates as a differential voltage magnitude detector, which generates opamp tail currents proportional to the magnitude (square) of the opamp's differential input voltage. Experimental results from a fabricated test chip verify current and slew rate enhancement between 900 and 1400% with respect to its initial value with <20% static current increase.